Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Explore a wealth of knowledge from professionals across various disciplines on our comprehensive Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To find the critical numbers of the function [tex]\( g(t) = t \sqrt{7 - t} \)[/tex] for [tex]\( t < 6 \)[/tex], follow these steps:
1. Write the function:
[tex]\[ g(t) = t \sqrt{7 - t} \][/tex]
2. Find the derivative of the function:
To determine the critical points, we first need to find the derivative [tex]\( g'(t) \)[/tex].
3. Rewrite [tex]\( g(t) \)[/tex]:
[tex]\[ g(t) = t (7 - t)^{\frac{1}{2}} \][/tex]
Now, we use the product rule to differentiate [tex]\( g(t) \)[/tex]. The product rule states that if [tex]\( u(t) = t \)[/tex] and [tex]\( v(t) = (7 - t)^{\frac{1}{2}} \)[/tex], then:
[tex]\[ g'(t) = u'(t)v(t) + u(t)v'(t) \][/tex]
4. Differentiate [tex]\( u(t) \)[/tex] and [tex]\( v(t) \)[/tex]:
[tex]\[ u(t) = t \implies u'(t) = 1 \][/tex]
[tex]\[ v(t) = (7 - t)^{\frac{1}{2}} \implies v'(t) = \frac{1}{2} (7 - t)^{-\frac{1}{2}} \cdot (-1) = -\frac{1}{2} (7 - t)^{-\frac{1}{2}} \][/tex]
5. Apply the product rule:
[tex]\[ g'(t) = 1 \cdot (7 - t)^{\frac{1}{2}} + t \left(-\frac{1}{2} (7 - t)^{-\frac{1}{2}}\right) \][/tex]
Simplify this expression:
[tex]\[ g'(t) = (7 - t)^{\frac{1}{2}} - \frac{t}{2} (7 - t)^{-\frac{1}{2}} \][/tex]
[tex]\[ g'(t) = \frac{2(7 - t) - t}{2 (7 - t)^{\frac{1}{2}}} \][/tex]
[tex]\[ g'(t) = \frac{14 - 3t}{2 \sqrt{7 - t}} \][/tex]
6. Set the derivative equal to zero to find critical points:
[tex]\[ \frac{14 - 3t}{2 \sqrt{7 - t}} = 0 \][/tex]
This implies:
[tex]\[ 14 - 3t = 0 \][/tex]
Solving for [tex]\( t \)[/tex]:
[tex]\[ 14 = 3t \][/tex]
[tex]\[ t = \frac{14}{3} \][/tex]
Therefore, the critical number of the function [tex]\( g(t) = t \sqrt{7 - t} \)[/tex], for [tex]\( t < 6 \)[/tex], is:
[tex]\[ t = \frac{14}{3} \][/tex]
So, the critical number is [tex]\( \frac{14}{3} \)[/tex].
1. Write the function:
[tex]\[ g(t) = t \sqrt{7 - t} \][/tex]
2. Find the derivative of the function:
To determine the critical points, we first need to find the derivative [tex]\( g'(t) \)[/tex].
3. Rewrite [tex]\( g(t) \)[/tex]:
[tex]\[ g(t) = t (7 - t)^{\frac{1}{2}} \][/tex]
Now, we use the product rule to differentiate [tex]\( g(t) \)[/tex]. The product rule states that if [tex]\( u(t) = t \)[/tex] and [tex]\( v(t) = (7 - t)^{\frac{1}{2}} \)[/tex], then:
[tex]\[ g'(t) = u'(t)v(t) + u(t)v'(t) \][/tex]
4. Differentiate [tex]\( u(t) \)[/tex] and [tex]\( v(t) \)[/tex]:
[tex]\[ u(t) = t \implies u'(t) = 1 \][/tex]
[tex]\[ v(t) = (7 - t)^{\frac{1}{2}} \implies v'(t) = \frac{1}{2} (7 - t)^{-\frac{1}{2}} \cdot (-1) = -\frac{1}{2} (7 - t)^{-\frac{1}{2}} \][/tex]
5. Apply the product rule:
[tex]\[ g'(t) = 1 \cdot (7 - t)^{\frac{1}{2}} + t \left(-\frac{1}{2} (7 - t)^{-\frac{1}{2}}\right) \][/tex]
Simplify this expression:
[tex]\[ g'(t) = (7 - t)^{\frac{1}{2}} - \frac{t}{2} (7 - t)^{-\frac{1}{2}} \][/tex]
[tex]\[ g'(t) = \frac{2(7 - t) - t}{2 (7 - t)^{\frac{1}{2}}} \][/tex]
[tex]\[ g'(t) = \frac{14 - 3t}{2 \sqrt{7 - t}} \][/tex]
6. Set the derivative equal to zero to find critical points:
[tex]\[ \frac{14 - 3t}{2 \sqrt{7 - t}} = 0 \][/tex]
This implies:
[tex]\[ 14 - 3t = 0 \][/tex]
Solving for [tex]\( t \)[/tex]:
[tex]\[ 14 = 3t \][/tex]
[tex]\[ t = \frac{14}{3} \][/tex]
Therefore, the critical number of the function [tex]\( g(t) = t \sqrt{7 - t} \)[/tex], for [tex]\( t < 6 \)[/tex], is:
[tex]\[ t = \frac{14}{3} \][/tex]
So, the critical number is [tex]\( \frac{14}{3} \)[/tex].
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.